Knowledge, Subjective Norm, Attitude, Perceived Behavior Control, Intentions About Hemoglobin in Pandemic Pregnant Women - Maria Agnes Kun Mawardani; Kuswandewi Mutyara; Siska Wiramihardja (Syntax Corporation Indonesia, 2023)
Anemia will increase the risk of miscarriage, giving birth to babies with low birth weight, born prematurely, the risk of bleeding before and or during delivery which can cause the death of the mother and baby. According to the Indonesian Ministry of Health, in 2021, Banten Province is part of the 6 provinces that contribute 50% of maternal mortality cases. The purpose of this study was to analyze the effect of anemia and nutrition education on hemoglobin levels in anemic pregnant women in primary care during the COVID-19 pandemic. This study uses a quasi-experimental design with the nonequivanlent control group design. A sample of 40 pregnant women with anemia in the second trimester in Primary Services in Tangerang City, Banten Province. Consisting of 20 pregnant women in the experimental group and 20 people in the control group. Anemia and nutrition education is given to pregnant women individually at the first visit for ANC and follow-up education via WA/SMS every week for 4 weeks and during ANC visits primary data is collected using a semi-structured questionnaire for interviews and hemoglobin levels are also checked. at the start of the ANC visit and 4 weeks later. Data were collected after 4 weeks for anemia and nutrition education intervention and data were analyzed using T test, Wilcoxon test, Mann Whitney test. Active collaboration support between medical personnel and pregnant women through online media Whatsapp/SMS reminder. Effect of anemia and nutrition education on hemoglobin levels in anemic pregnant women in primary care during the Covid 19 period.